RESERVOIR PROPERTIES OF CONSOLIDATED TERRIGENOUS ROCKS OF CAMBRIAN PERIOD OF THE EASTERN SLOPE OF THE LVIV PALEOZOIC DEPRESSION - Vyzhva, S.; Onyshchuk, V.; Onyshchuk, I.; Reva, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper concerned the researches of porosity and permeability properties of consolidated terrigenous reservoir rocks of Cambrian period of the Eastern slope of the Lviv depression. The purpose of the research was to study the petrophysical parameters of the consolidated reservoir rocks, as the basis of the integrated analysis of their physical properties. Such reservoir parameters as the open porosity factor and void factor, permeability coefficient and residual water saturation factor have been studied. The article presents the limits of changes and the average values of porosity and permeability properties of rocks, and the classification of their reservoir properties. On the basis of capillarimetric research, an evaluation of the structure of the void space of rocks was made. The correlation analysis has allowed to establish a series of empirical relationships between the reservoir parameters (density, porosity coefficient, effective porosity factor and residual water saturation factor) and, also, to determine correlation dependences between porosity coefficients measured in atmospheric and reservoir conditions. These relationships can be used in the data interpretation of geophysical studies of wells and in the modeling of porosity and permeability properties of consolidated rocks of the Eastern slope of the Lviv depression.